Actor Relations in the Change of Shape and Space in the Rumah Gadang of Balai Kaliki Traditional Village - Putri, Azani Zalika; Ekomadyo, Agus S.; Triharini, Meirina (Jurnal Koridor, 2023)
Rumah Gadang is a traditional building that represents the cultural identity of Minangkabau Tribe in West Sumatera. This traditional building is a cultural heritage that must be preserved. However, preservation led to many changes in the form and space of traditional buildings. Rumah Gadang which is located in Kampung Adat Balai Kaliki, Payakumbuh City West Sumatera has a level of change in minor and major. That matter could happen because of differences in the network of actor relations in each building. The factor of actor relations has an impact to change the preservation of traditional buildings, thus providing a new perspective on the preservation of traditional buildings. Therefore, this research aims to observe the changes that occur in the Rumah Gadang located in Kampung Adat Balai Kaliki through actor network’s perspective. Completion of this research using a qualitative methodology with Actor Network Theory (ANT) method by examining changes that occur in Rumah Gadang holistically, which is through a study the relations between the actors involved in that building to discorver the factors that cause the changes. This research find that the relation of actors involved in each Rumah Gadang determines the quantity of building changes. The result is charted using sosiotechnogram to know the strong actors in actor relations from each Rumah Gadang. Therefore, this research could be the basis for appropriate practices of preserving Rumah Gadang traditional building.